Análisis de los armónicos generados en los inversores de los sistemas fotovoltaicos autónomos residenciales. . - Barrionuevo Simbaña, Alex Paul (2023)
The use of technologies such as photovoltaic systems allow the generation of alternating current from direct current; this result is obtained through a set of electrical and electronic equipment. One of these pieces of equipment is the inverter, the same one that is responsible for supplying alternating current to the electrical installation. Its electrical topology composed of electronic switching elements generates distortions in the quality of electrical energy that, together with non-linear loads, can cause damage to different equipment. This project focuses on the analysis of these distortions known as Harmonics, which by collecting data through the Fluke 435 energy analyzer allows us to obtain measurements of the three autonomous photovoltaic systems analyzed. These generated harmonics must comply with the parameters established in the ARCERNNR 002/20 regulation and IEEE 519, regulations that establish the distortion limits in an electrical system. The results obtained from the measurement indicate the presence of harmonics in the three systems analyzed, with SFV N°2 and N°3 being the ones that present the greatest irregularities. To mitigate these disturbances in the electrical installation, the use of passive filters is proposed, the same ones that allow controlling the presence of these harmonic components. The filter implemented and simulated in Simulink allows reducing the third order harmonic that initially presents a 9.14% distortion above the 4% limit established in the regulations to 3.22%, in addition the THD is reduced from 21.96% to 8.04%.